ANALISIS PENGARUH CUSTOMER RELATIONSHIP MARKETING DAN LAYANAN PURNA JUAL TERHADAP KEPUASAN PELANGGAN - Hardiyanti Lestari Kusuma (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
The purpose of research is to know and analyze the strength and direction of influence customer relationship marketing and after sales service to customer satisfaction at PT AUTO 2000 Daan Mogot. This type of research used is quantitative research with explanative design. The sample was taken by accidental sampling technique with 69 respondents. Data obtained through questionnaires developed based on indicators of each variable and measured by Likert scale. Data were analyzed by multiple linear regression. The results showed that: (1) customer relationship marketing partially significant effect on customer satisfaction (2) after sales service partially significant effect on customer satisfaction and (3) simultaneously, customer relationship marketing and after sales service significantly influence customer satisfaction.